Digital Game-Based Phonics Instruction Promotes Print Knowledge in Pre-Readers at Cognitive Risk for Dyslexia - Vanden Bempt, Femke; Economou, Maria; Van Herck, Shauni; Vanderauwera, Jolijn; Glatz, Toivo; Vandermosten, Maaike; Wouters, Jan; Ghesquière, Pol (Frontiers in Psychology, 2021)
Dyslexia is targeted most effectively when (1) interventions are provided preventively, before the onset of reading instruction, and (2) remediation programs combine letter-sound training with phoneme blending. Given the growing potential of technology in educational contexts, there has been a considerable increase of letter-sound trainings embedded in digital serious games. One such intervention is GraphoGame. Yet, current evidence on the preventive impact of GraphoGame is limited by the lack of adaptation of the original learning content to the skills of pre-readers, short training duration, and a restricted focus on explicitly trained skills. Therefore, the current study aims at investigating the impact of a preventive, and pre-reading adapted GraphoGame training (i.e., GraphoGame-Flemish, GG-FL) on explicitly trained skills and non-specifically trained phonological and language abilities. Following a large-scale screening (N = 1225), the current study included 88 pre-reading kindergarteners at cognitive risk for dyslexia who were assigned to three groups training either with GG-FL (n = 31), an active control game (n = 29), or no game (n = 28). Before and after the 12-week intervention, a variety of reading-related skills were assessed. Moreover, receptive letter knowledge and phonological awareness were measured every three weeks during the intervention period. Results revealed significantly larger improvements in the GG-FL group on explicitly trained skills, i.e. letter knowledge and word decoding, without finding transfer-effects to untrained phonological and language abilities. Our findings imply a GG-FL-driven head start on early literacy skills in at-risk children. A follow-up study should uncover the long-term impact and the ability of GG-FL to prevent actual reading failure.